2013
DOI: 10.1074/jbc.m113.498774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Auto- and Hetero-catalytic Maturation of a Thermostable Subtilase from Thermophilic Bacillus sp. WF146

Abstract: Background:The autocatalytic maturation mechanisms of subtilases are well known, but little is known about their hetero-catalytic maturation. Results: The N-terminal propeptide of the WF146 protease can be removed via both cis-and trans-processing reaction-initiated maturation pathways. Conclusion: The WF146 protease is intrinsically able to mature either autocatalytically or hetero-catalytically. Significance: Our work provides new insights into maturation mechanisms of subtilases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…5C and D, ϪM). We found that the cisprocessed N* of BprL⌬C912, BprL⌬C912-S258C, BprL⌬C678, or BprL⌬C678-S258C coeluted with Ia or Ia= from an Ni 2ϩ -charged column (data not shown), implying that the cleaved N* was still bound to Ia or Ia= to form an autoprocessed complex (N*-Ia or N*-Ia=), as has been reported for other subtilisins (28,29). In the presence of the active 45-kDa mature enzyme, either N*-Ia or N*-Ia= was trans processed into the 45-kDa mature form (Fig.…”
Section: Fig 4 In Vitro Processing Of Bprl and Its Variants (A To C)supporting
confidence: 66%
See 2 more Smart Citations
“…5C and D, ϪM). We found that the cisprocessed N* of BprL⌬C912, BprL⌬C912-S258C, BprL⌬C678, or BprL⌬C678-S258C coeluted with Ia or Ia= from an Ni 2ϩ -charged column (data not shown), implying that the cleaved N* was still bound to Ia or Ia= to form an autoprocessed complex (N*-Ia or N*-Ia=), as has been reported for other subtilisins (28,29). In the presence of the active 45-kDa mature enzyme, either N*-Ia or N*-Ia= was trans processed into the 45-kDa mature form (Fig.…”
Section: Fig 4 In Vitro Processing Of Bprl and Its Variants (A To C)supporting
confidence: 66%
“…It is known that replacing the catalytic residue Ser with Ala abolishes the activity of subtilases but does not affect enzyme folding (28,29). To investigate whether the multiple proteolytic processing of BprL occurs auto-or heterocatalytically, the culture supernatant of B. subtilis WB700(pBE2-bprLS258A) producing the active-site variant BprLS258A was subjected to SDS-PAGE and immunoblot analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major difference between the maturations of the two halolysins is that the Nep precursor can be trans-processed into its mature form by active Nep, but the SptC precursor is degraded by active mature SptC. Generation of the mature enzyme via transprocessing of the N-terminal propeptide of the precursor or the proform, either auto-or heterocatalytically, has also been described for other subtilases (27,(35)(36)(37)(38). In the precursor of the WF146 protease from thermophilic Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In the precursor of the WF146 protease from thermophilic Bacillus sp. WF146, a 12-residue linker peptide between the core domain of the N-terminal propeptide and the catalytic domain comprises a proteolytically sensitive region, but the catalytic domain adopts a stable conformation that is resistant to proteolysis, allowing the trans-processing reaction to occur auto-and heterocatalytically (38). Although the SptC precursor contains a five-residue linker peptide, its catalytic domain is susceptible to proteolysis.…”
Section: Discussionmentioning
confidence: 99%